Burden of autism spectrum disorder in Japan from 1992 to 2021 and its prediction until 2050: results from the GBD study - Liu, Jiabo; Xie, Xiaoyan; Li, Yunxi; Pu, Yiqi; Li, Yan; Yang, Lingling (Frontiers in Psychiatry, 2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental condition characterized by persistent deficits in social communication and interaction, alongside restricted, repetitive patterns of behavior. This study aimed to analyze the temporal trends and project the future burden of ASD in Japan. Using Global Burden of Disease (GBD) 2021 data, we analyzed prevalence, disability-adjusted life years (DALYs), and age-standardized rates (ASR) (1992-2021) through age-period-cohort modeling, joinpoint regression, and autoregressive integrated moving average (ARIMA) forecasting. Age-standardized prevalence rate (ASPR) increased significantly (Average Annual Percentage Change [AAPC]=0.2744; 95%CI:0.2606-0.2882), with males disproportionately affected (male-to-female ratio 4:1). By 2050, crude prevalence is projected to decline 14.2%, while ASPR will rise 18.0%. Japan’s ASD burden exceeds global averages, necessitating targeted interventions across the lifespan. These findings highlight the increasing burden of ASD in Japan and underscore the urgent need for enhanced healthcare planning and resource allocation.